(untitled) (El Hilo de la Fabula, 2018)
This article analyzes the relation between autobiography, reader and communicability in a work of great complexity, Jorge Semprún’s Autobiografía de Federico Sánchez. The problem of communicability intensifies with contemporary texts that are explicitly ideological. How do we read these works, especially when the values and belief systems expressed in them do not coincide with our own? The reception of this work is further complicated through the double exile of the writing subject and reader alike.